ANALISIS TINGKAT KEPERCAYAAN DIRI PESERTA DIDIK PROGRAM LINTAS MINAT PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 14 PALEMBANG - Mutiya Oktariani; Ikbal Barlian; Siti Fatimah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2017)
The purpose of this research was describe the confidence level of students in cross-interest program on economic subject at SMA N 14 Palembang. The research problem of this research was “how confidence level of students in cross-interest program on economic subject at SMA N 14 Palembang”. This research was a qualitative descriptive method. The population of this research was all of students X science grades of SMA N 14 Palembang. Fourty students from X science 2 were selected as sample of the research by using purposive sampling technique. Data triangulation technique was used to collect data such as questionare, observation, and interview. The data Milles and Hubberman method with data display shaped inverted pyramid based on the highest until the lowest indicator were used to analyze in this research. The highest indicator was that believing in your own ability with the persentage of 84,58% belongs to very high criteria, having the attitude of attention with the percentage of 83,92% belongs to very high criteria, responsibility with the percentage 81,39% belongs to very high criteria, daring to convey opinons with the percentage of 79,41% belongs to high criteria, having realistic expectations towards themselves with the percentage of 77,48% belongs to high criteria, and not easy to despair with the percentage of 75,44% belongs to high criteria.